2016
DOI: 10.1038/srep36039
|View full text |Cite
|
Sign up to set email alerts
|

Optogenetic activation of serotonergic terminals facilitates GABAergic inhibitory input to orexin/hypocretin neurons

Abstract: Orexin/hypocretin neurons play a crucial role in the regulation of sleep/wakefulness, primarily in the maintenance of wakefulness. These neurons innervate wide areas of the brain and receive diverse synaptic inputs including those from serotonergic (5-HT) neurons in the raphe nucleus. Previously we showed that pharmacological application of 5-HT directly inhibited orexin neurons via 5-HT1A receptors. However, it was still unclear how 5-HT neurons regulated orexin neurons since 5-HT neurons contain not only 5-H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…Then, 300 μL supernatant (plasma) was stored in a vial and kept at -80 °C until analysis. Once the blood collection was finished, some of the rats were perfused transcardially and immediately with ice-cold formalin (40 g/L) solution, and the brain and stomach were quickly removed and post-fixed by immersing in 40 g/L formalin solution at 4 °C overnight for immunohistochemistry (IHC) measurements[ 45 ]. Others of the rats were sacrificed by rapid decapitation and the hippocampus and gastric fundus (by another operator) were then isolated carefully, wrapped in foil and dropped in liquid nitrogen immediately and stored at -80 °C for ELISA or Western blot (WB) measurements[ 46 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, 300 μL supernatant (plasma) was stored in a vial and kept at -80 °C until analysis. Once the blood collection was finished, some of the rats were perfused transcardially and immediately with ice-cold formalin (40 g/L) solution, and the brain and stomach were quickly removed and post-fixed by immersing in 40 g/L formalin solution at 4 °C overnight for immunohistochemistry (IHC) measurements[ 45 ]. Others of the rats were sacrificed by rapid decapitation and the hippocampus and gastric fundus (by another operator) were then isolated carefully, wrapped in foil and dropped in liquid nitrogen immediately and stored at -80 °C for ELISA or Western blot (WB) measurements[ 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…The ELISA assays of MPO activity and the levels of 5-HT, GABA, BDNF and nesfatin-1 were analyzed as described by the instructions of the ELISA kits and the methods described previously[ 32 , 41 - 44 ]. The IHC and WB tests of the levels of 5-HT1AR in the hippocampal CA1 subfield or the mucosa of the gastric fundus were also performed using the methods reported previously[ 45 , 46 ].…”
Section: Methodsmentioning
confidence: 99%
“…OF and orexin-EGFP ( OE ) (Yamanaka et al, 2003) mice of both sexes, aged 2-5 months, were used for electrophysiological recordings. Brain slice preparations and subsequent electrophysiological recording were modified from a previously published protocol (Chowdhury and Yamanaka, 2016). Briefly, mice were deeply anesthetized using isoflurane (Wako) and decapitated at around 11:00 AM.…”
Section: Methodsmentioning
confidence: 99%
“…These inputs include GABAergic neurons in the preoptic area, serotonergic neurons in the dorsal and median raphe nuclei, central amygdala, basal forebrain cholinergic neurons, the bed nucleus of the stria terminalis, supraventricular zone, and the dorsomedial, lateral and posterior hypothalamus (Sakurai et al, 2005; Yoshida et al, 2006). Recently, we reported that serotonergic neurons in the raphe nucleus inhibit orexin neurons both directly and indirectly (Chowdhury and Yamanaka, 2016). Orexin neurons are also found to respond to multiple humoral factors and neuropeptides (Inutsuka and Yamanaka, 2013; Sakurai, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Serotonin and noradrenaline hyperpolarize all orexin neurons through two receptors coupled to inhibitory Gi proteins (5HT1A and alpha 2A receptors, respectively) and subsequently activate protein-coupled inwardly rectifying potassium channels. Recent optogenetic methods allowed to confirm that the activation of serotoninergic neuron terminal inhibits orexin neurons either directly (via 5-HT1A receptor) or indirectly (via facilitation of GABAergic-inhibitory inputs) [25]. Dopamine also hyperpolarizes orexin neurons possibly by an indirect action through alpha 2A receptor [26], and glycine inhibits the activity of orexin neurons either directly and indirectly [27].…”
Section: Orexinergic Neurons Their Receptors and Physio-pharmacologmentioning
confidence: 99%